2019
DOI: 10.3847/1538-4357/ab2b40
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Disruption Events in Active Galactic Nuclei

Abstract: A fraction of tidal disruption events (TDEs) occur in active galactic nuclei (AGNs) whose black holes possess accretion disks; these TDEs can be confused with common AGN flares. The disruption itself is unaffected by the disk, but the evolution of the bound debris stream is modified by its collision with the disk when it returns to pericenter. The outcome of the collision is largely determined by the ratio of the stream mass current to the azimuthal mass current of the disk rotating underneath the stream footp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 40 publications
4
90
0
Order By: Relevance
“…This finding does not explain the Tadhunter et al (2017) result of an elevated tidal disruption event rate in AGN, nor does it rule out the coexistence of tidal disruption events with preexisting accretion flows (e.g. Chan et al 2019).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This finding does not explain the Tadhunter et al (2017) result of an elevated tidal disruption event rate in AGN, nor does it rule out the coexistence of tidal disruption events with preexisting accretion flows (e.g. Chan et al 2019).…”
Section: Discussionmentioning
confidence: 80%
“…One such potential event has been observed by Tadhunter et al (2017), who additionally claim that this event also represents a highly elevated occurrence rate of tidal disruptions within AGN. Theoretical models of the hydrodynamic interaction between a tidal disruption debris stream and a preexisting accretion disk have been recently presented by Chan et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hung et al 2017). However, recent simulations of TDEs occurring in AGN have shown that the spectrum of the resulting transient may not look like a standard TDE and it is even uncertain in which energies the radiation emerges from the event (Chan et al 2019). Furthermore, substantial reprocessing of the TDE emission may have occurred within the dense BLR clouds.…”
Section: Tidal Disruption Eventmentioning
confidence: 99%
“…Recently, Chan et al (2019) have simulated the interaction of the debris stream with a pre-existing accretion disc, when the disruption occurs in an AGN. They have used the grid-based code Athena++ and find that the stream can excite significant inflow in the disc (strongly super-Eddington), while the emergent radiation is expected to be close to the Eddington value.…”
Section: Disc Formationmentioning
confidence: 99%